Attention to the body! Comparing the connection between interoceptive abilities and somatic complaints of women with and without history of intimate partner violence - Joana Machorrinho; José Marmeleira; Graça Duarte Santos; Guida Veiga (Women's Health)
Background: Somatic complaints are a critical burden to women, particularly to those women who survived intimate partner violence (IPV). The way women feel, perceive, and relate to their own body, that is, interoception, seems to have a significant role in the pathway to somatic complaints. However, to the best of our knowledge, no study has yet explored the relationship between interoception and somatic complaints of women survivors of IPV. Objectives: To deepen the understanding of the underlying interoceptive mechanisms of somatic complaints experienced by women survivors of IPV. Design: Cross-sectional study. Method: Women with ( N  = 44) and without ( N  = 52) history of IPV were assessed regarding interoceptive accuracy, interoceptive sensibility, and somatic complaints. Associations between both variables in each group were examined, and a hierarchical regression analysis assessed to what extent somatic complaints were explained by the interoceptive abilities, with the mediating role of IPV group membership. Results: Women survivors of IPV reported more somatic complaints ( p  < 0.001), which were negatively associated with interoceptive attention regulation. The opposite association was found in women who have never experienced IPV. For the IPV group, the interoceptive attention regulation, added to age and the index of the violence suffered, explains 43% of the variance in somatic complaints. Conclusion: The findings suggest that for women with history of IPV, but not for those without, the ability to regulate the attention given to bodily sensations is a mediator of women’ somatic complaint. Thereby we suggest that interoceptive attention regulation can be a promising therapeutic aim, for women recovering from IPV.